A ludicidade na educação: aprender brincando - PEREIRA, Vanusa de Melo Martins (2019)
This paper presents the theme of playfulness, thus enabling us to further understand the aspects of Brazilian education, and especially the school of the city of Muana. In this context, an ethnographic research was conducted at the Santa Rita de Cássia School for 4 months, with the purpose of reflecting how playfulness is triggered by the didactic resource in the teaching and learning process of the 1st year of elementary school. The methodological procedures followed the ethnographic path, through participant observation, which allows the observation of reality. As theoretical references of great relevance in playfulness and with regard to child development, I called Abreu (2013), Vygotsky (1994), (1984), Antunes (1998), among others. The results obtained were: playfulness is triggered by the didactic resource in the 1st grade elementary school class of the researched school; The teacher uses games, toys and games in her activities, helping the development in learning; and I could see that playfulness is present in the classroom, on the colorful walls with posters, with toys and songs of wheels, awakening in children an additional desire to learn, and thus, obtaining better results in teaching learning.